A secure chat application based on pure peer-to-peer architecture - Mohamed, Mohamad Afendee; Muhammed, Abdullah; Man, Mustafa (Science Publications, 2015)
Chat application is increasingly used as an alternative to older communication technologies such as telephony and telegraph. Equipped with advanced features, people can use it for education, business and socialize. Basic requirement for chatting is an ability to exchange text messages, however, recent releases include support for audio and video communications. For some reasons, peer-to-peer now turned out to be a popular architecture and as such, it becomes a choice for developing chat applications such as Skype. Skype however, makes use of centralized server for user registration, login and buddy list. Indeed, this idea could be disastrous in the event of a compromise. In this study, we proposed a chat application that is based on pure peer-to-peer architecture that totally rid of centralized or third party elements. The system is controlled by the users and its security is autonomously managed by the communicating parties. Each user will have their own database for peer's profiles and communication parties authenticate among each other before exchanging messages. The main contribution of this paper is a state-of-the-art chat application having completely been designed with build in security measures.